Migratory experiences: Good local practices in South American cities - Palacios Sanabria, María Teresa (2021)
This article is the result of the research from two projects led by the University of Rosario, Colombia, and presents contributions to the guarantee of the human rights of the migrant population. In the first place, itdevelops an approach to the characteristics, actors and results of the concept of good practices in migration matters in Argentina, Colombia, Ecuador and Peru in the 2014-2018 period; and unfolds the preliminary elements for the construction of a good practices typology with a human rights approach through the illustration of local experiences in the Southern Cone for capital,border and intermediate cities of the selected countries.The methodology used was inductive-deductive, promoting a permanent dialogue between theory and practice. The central contributions of this research focus on the identification of certain trends in capital cities, where there is an oscillation between contingency and sustainable actions, which affects the integration of the migrant population to the host society. In border cities, the greatest risks and the widest possibilities of support from state and international entities and social organizations are evidenced; while,in intermediate cities, the greatest opportunities are envisaged through the incorporation of local approaches that include guarantee of rights.